2015
DOI: 10.1093/gbe/evv149
|View full text |Cite
|
Sign up to set email alerts
|

Chemoreceptor Evolution in Hymenoptera and Its Implications for the Evolution of Eusociality

Abstract: Eusocial insects, mostly Hymenoptera, have evolved unique colonial lifestyles that rely on the perception of social context mainly through pheromones, and chemoreceptors are hypothesized to have played important adaptive roles in the evolution of sociality. However, because chemoreceptor repertoires have been characterized in few social insects and their solitary relatives, a comprehensive examination of this hypothesis has not been possible. Here, we annotate ∼3,000 odorant and gustatory receptors in recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
211
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(240 citation statements)
references
References 63 publications
15
211
1
Order By: Relevance
“…Our findings, taken together with those of previous evolutionary studies (31,39), suggest that dynamic gene family evolution, including gene expansion and sequence evolution, has played an essential role in the evolution of ant communication and sociality. This discovery provides further evidence for the importance of chemical communication in ant biology, as well as a striking example of the role of novel genes in the evolution of social behavior.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our findings, taken together with those of previous evolutionary studies (31,39), suggest that dynamic gene family evolution, including gene expansion and sequence evolution, has played an essential role in the evolution of ant communication and sociality. This discovery provides further evidence for the importance of chemical communication in ant biology, as well as a striking example of the role of novel genes in the evolution of social behavior.…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, Zhou et al (39) found that the 9-exon subfamily has the highest selection coefficient of all ant OR subfamilies. Although some analyses have indicated that ant ORs do not undergo higher positive selection than those of solitary hymenopterans (39, 43), Zhou et al (39) found evidence for higher positive selection in ORs in the ancestors of extant ants, consistent with our finding of rapid gene expansion along that branch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we concentrated particularly on two hallmarks of insect eusociality, as previously described for Hymenoptera, with the expectation that similar patterns occurred along with the emergence of termites. These are the evolution of a sophisticated chemical communication, which is essential for the functioning of a eusocial insect colony 3,14,15 , and major changes in gene regulation along with the evolution of castes 9,10 . We also tested whether transposable elements spurred the evolution of gene families that were essential for the transition to eusociality.…”
mentioning
confidence: 99%
“…Some chemical communication genes likely have highly conserved functions as indicated by conserved sequences and antennal expression of core sets of single-ortholog odorant binding proteins (OBPs) and chemosensory proteins (CSPs) [58,59]. However, among the 330 AE 26 (mean AE standard deviation) odorant and the 80 AE 67 gustatory receptors identified in each of eight ant species, >30% were taxonspecific [60]. Frequent gene duplications and losses suggest that many chemical communication genes are involved in adaptive processes in response to changing environments or arms races.…”
Section: Roles Of Chemical Communication Genes In Colony Lifementioning
confidence: 99%